Tar baby - Morrison, Toni. (London : Vintage, 2004)
A beautiful African-American woman of privilege finds herself attracted to the kind of man she has dreaded since childhood: uneducated, violent, and contemptuous of her.
First published: 1981.
Young Adult
Keywords: African Americans -- Race identity -- Fiction; Man-woman relationships -- Fiction; African Americans -- Race identity -- Fiction; Love stories; Man-woman relationship -- Fiction